Handover management of millimeter wave vehicular communication - Soh, Nicholas Zi Xing (2019)
This report presents details and application of a simulation software named NSZXSIM, which can be used to calculate the received signal strength in an ideal environment; an area of 7 cells, each having a base station in the centre and covering a small area of 100 by 100 metres. This is designed for the millimetre wave which has a carrier frequency of 20GHz. It incorporates the calculation using the Euclidean distance from the user location to the base station, to receive the signal strength and show when it will be handed over to another base station. This report also provides examples to demonstrate how the simulation can be used.